The influence of trade unions, collective labor agreements and industrial relations on the welfare of workers at PT.Uniplastindo Interbuana. - Dadang Heri Kusumah; Tri Wahyu Wirjawan; Nurmubin Dalidjo (The Management Journal of Binaniaga, 2021)
Abstract.The background of this research is to find out whether trade unions, collective labor agreements, and industrial relations have an effect on workers' welfare.In this research, data were collected using questionnaires as research data from 60 respondents from a total population of 144 workers who are members of trade unions at PT. Uniplastindo Interbuana. Hypothesis testing conducted using the SPSS version 22 application partially with the comparison method of the tcount value with the ttable value resulted in the conclusion that Variable X1, (tcount 3.539 > ttable 1.673) then H1 or the first hypothesis was accepted. Variable X2, (tcount 3.057 > ttable 1.673) then H2 or the second hypothesis is accepted. Variable X3, (tcount 2.864 > ttable 1.673) then H3 or the third hypothesis is accepted.